Five winters of pneumococcal serotype replacement in UK carriage following PCV introduction. Issue 17 (21st April 2015) - Gladstone, Rebecca A.; Jefferies, Johanna M.; Tocheva, Anna S.; Beard, Kate R.; Garley, David; Chong, Wei Wei; Bentley, Stephen D.; Faust, Saul N.; Clarke, Stuart C.
Highlights: PCV7 serotype replacement was near complete 5 years after PCV7 introduction. The carriage rate remained stable through out the 5 year period. Serotypes unique to PCV13 significantly decreased by the final winter. Clonal expansion of existing genotypes was primarily responsible for replacement. Continued surveillance is needed to monitor replacement until equilibrium is reached. Abstract: The seven-valent pneumococcal conjugate vaccine (PCV7) was added to the UK national immunisation programme in September 2006. PCV13 replaced PCV7 in April 2010. As carriage precedes disease cases this study collected carried pneumococci from children each winter from 2006/7 to 2010/11 over PCV introduction. Conventional microbiology and whole genome sequencing were utilised to characterise pneumococcal strains. Overall prevalence of pneumococcal carriage remained stable. Vaccine serotypes (VT) decreased ( p < 0.0001) with concomitant increases in non-vaccine serotypes (NVT). In winter 2010/11 only one isolate of PCV7 VT was observed (6B). PCV13 unique VTs decreased between winters immediately preceding and following PCV13 introduction ( p = 0.04). Significant decreases for VTs 6B, 19F, 23F (PCV7) and 6A (PCV13) and increases for NVT 21, 23B, 33F and 35F were detected. The serotype replacement was accompanied by parallel changes in genotype prevalence for associated sequence types with clonal expansion contributing to replacement. By winter 2010/11, serotype coverage of PCV7 and PCV13 was 1% and 11% respectively. VT replacement was observed for PCV7 and PCV13 serotypes. Conjugate vaccine design and use requires continuous monitoring and revision.